Nevada's Academic-Practice Collaboration: Public Health Preparedness Possibilities Outside an Academic Center - Clements-Nolle, Kristen (Association of Schools of Public Health, 2005)
The Nevada State Health Division developed a local academic-practice partnership with the University of Nevada Reno's Master of Public Health Program to assess the bioterrorism risk communication, information, response, and training needs of professional and public stakeholder groups throughout Nevada. Between October 16, 2002, and April 13, 2004, 22 needs assessment focus groups and 125 key informant interviews were conducted to gather information on the diverse needs of the stakeholders. The themes that emerged from these activities included the need for effective pre-event education and training; a coordinated and responsive public health preparedness infrastructure; honest, accurate, and timely communication in the event of a bioterrorism situation; and appropriate information dissemination methods and technology. The data collected through this needs assessment gave the Nevada State Health Division vital information to plan public health preparedness initiatives. The establishment of local academic-practice partnerships for states without a Centers for Disease Control and Prevention-funded Academic Center for Public Health Preparedness is an effective way for health departments to develop their public health preparedness infrastructure while simultaneously training the future public health workforce.